Transient transformation of surface plasmon due to time variations in dielectric permittivity of nanowire environment - Stognii, N. P.; Sakhnenko, N. K. (IEEE, 2016)
In this paper, a 2D problem of a surface plasmon transformation due to a time variation of silver nanowire environment is analytically solved. Solution of the problem is derived in the form of the Laplace transform. Accurate time domain inversion makes it possible to analyze transient and steady state regimes.
Keywords: Time domain analysis; surface plasmons; time varying domain; nanowire